Storied experiences of the Havelock North drinking water crisis: A case for a ‘narrative green victimology’ - Monod de Froideville, Sarah (International review of victimology, 2022)
The number of victims from environmental harm far exceeds that from everyday property and interpersonal crime, yet little is known about the experience of environmental victimisation. This paper makes a case for a narrative green victimology to advance scholarship about environmental victims, drawing on data from interviews with persons affected by a waterborne outbreak of campylobacter in the small town of Havelock North, New Zealand, in August 2016. Findings demonstrate that understandings of environmental harm are developed in narratives, with narratives. In particular, participants’ stories of harm and victimisation revealed fragments of larger, cultural narratives about sacrifice, nation-building, motherhood, and environmental purity, each of which affected their understanding of the impact of the outbreak on their autonomy as agentive persons. It is proposed that a narrative green victimology offers environmental victimology a platform upon which it can foot its frameworks.